2015
DOI: 10.1055/s-0035-1560705
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aliphatic Azides by Photoinduced C(sp3)–H Azidation

Abstract: A photoinduced synthesis of aliphatic azides was achieved in a single step starting from the parent cyclic alkanes, as well as from tetrahydrofuran and pyrrolidine derivatives. The reaction proceeds via direct azidation of C(sp 3)-H bonds in the presence of 4-benzoylpyridine under photoirradiation conditions utilizing tosyl azide as the azide source. The chemoselective C-H mono-azidation at room temperature and the formation of azide compounds in spite of their potential photolability are the key features of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
(7 reference statements)
0
23
0
Order By: Relevance
“…In another instance, the preparation of alkyl azides through a C(sp 3 )–H to C–N bond conversion, making use of 4‐BzPy as the photocatalyst and tosyl azide in the role of an N 3 ‐transfer agent, has been reported. The reaction was applied to tetrahydrofuran and pyrrolidine derivatives, as well as alkanes, and afforded the desired products in a single‐step fashion under mild reaction conditions …”
Section: Direct Hat Approachesmentioning
confidence: 99%
“…In another instance, the preparation of alkyl azides through a C(sp 3 )–H to C–N bond conversion, making use of 4‐BzPy as the photocatalyst and tosyl azide in the role of an N 3 ‐transfer agent, has been reported. The reaction was applied to tetrahydrofuran and pyrrolidine derivatives, as well as alkanes, and afforded the desired products in a single‐step fashion under mild reaction conditions …”
Section: Direct Hat Approachesmentioning
confidence: 99%
“…Among reported aliphatic C–H functionalization reactions, C–H azidation has proven to be particularly useful due to the unique photophysical and chemical reactivity of the azido group. 6 14 In 1996, Zhdankin 8 reported that the reaction of simple hydrocarbons with azidoiodane 1 in the presence of benzoyl peroxide led to the selective azidation of 3° and activated 2° C–H bonds in moderate to good yield. 9 11 Hartwig recently discovered that Fe/PyBOX catalysts promote aliphatic C–H azidation with 1 under milder conditions, allowing the labeling of complex natural products with high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The yield of 2 a remained at 66 % using the alkylsulfonyl oxime as the aldoxime precursor (entry 4). Screening of aryl ketones revealed that electron‐deficient perfluorobenzophenone ((C 6 F 5 ) 2 CO) and 4‐BzPy led to higher yields of 2 a compared to Ph 2 CO (71 % and 88 %, entries 5 and 6). The reaction using ( p ‐methoxy)benzenesulfonylmethanal O ‐benzyloxime and 4‐BzPy in CH 2 Cl 2 gave the highest yield of 2 a (90 % yield determined by NMR spectroscopy, 85 % yield of isolated products, entry 7) and these conditions were used in subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Expulsion of the sulfonyl radical from C affords the aldoxime 2 as a product, completing the substitutive introduction of the aldoxime functionality to the carbon chain of 1 . The released sulfonyl radical accepts a hydrogen atom from the ketyl‐type radical B to regenerate 4‐BzPy, most likely through the formation of the sulfonamide D , which is generated by coupling of the released sulfonyl radical and B …”
Section: Methodsmentioning
confidence: 99%